Bilateral choroidal colobomas: A rare case report and literature review - Dahal, Polina; Shrestha, Hari; Shrestha, Anki; Mishra, Ishani (Journal of Chitwan Medical College, 2024)
Ocular colobomas are congenital gaps in the ocular anatomy, namely choroidal colobomas. It happens when the embryonic fissure fails to fuse, leaving a chronic defect. Measuring just 0.14% of eye patients, choroidal colobomas might be inherited or spontaneous, making genetic identification difficult. Although colobomas typically cause no symptoms and are discovered by accident, they can sometimes cause vision loss. Numerous abnormalities are linked to colobomas, and their consequences—such as retinal detachment—call for specialized treatments such as preventive laser therapy. We report the case of an eighteen-year-old female patient with bilateral choroidal coloboma, presenting with iris coloboma and impaired vision. This study emphasizes how crucial it is to identify colobomas as soon as possible for the best possible care.